Analisis Pengelolaan Keuangan Desa Menggunakan Aplikasi Sistem Keuangan Desa (Siskeudes) di Desa Kabupaten Bogor - Setiawan, Arbi; Prihatni, Rida; Handarini, Dwi (Jurnal Akuntansi, Perpajakan dan Auditing, 2024)
This study is to determine the implementation of the village financial system (Siskeudes) in two villages of Bogor Regency and its obstacles starting from the stages of planning, implementation, administration, reporting and accountability in accordance with Permendagri Number 20 of 2018 concerning village financial management. Two villages in Bogor Regency, namely Bojonggede Village (Suburban Village) and Pamegarsari Village (Tourism Village). This research uses a descriptive-qualitative approach with interview and documentation techniques. The consequences of the study display that Bojonggede Village and Pamegarsari Village manipulate village price range using the siskeudes application according with Permendagri Number 20 of 2018, but the information media for the APBDes report in Pamegarsari Village is only through banners and the village website is not running well. The obstacle is the change in the budget in the preparation of the GWP (Government Work Plan) which must be based on the Regent Regulation and the change of the village cash account this year from Bank BRI to Bank BJB because it is to facilitate transaction matters.